Study on Congestion Management by Changing Generator Participation Factor - Rane , P. R.; Ghawghawe, N. D. (Techniques and Innovation in Engineering Research and Technology Vol. 5, 2023)
Power system congestion management is a demanding undertaking, and the power industry reorganization process makes it even more difficult. One significant problem is precisely estimating the transfer capability remaining in the system for future transactions, which is referred to as Available Transfer Capability (ATC). The generator participation factor is utilized in this research to calculate the ATC of a network created in Power Word Simulator14. The participation factor measures how the generator's real power output changes in response to load demand. The ATC of the network is determined in this article by selecting different generator participation factors. The maximum permitted load at a bus can be altered by modifying the participation factors of generators without creating insecurity to the power system network and so can be employed as a tool for congestion management.